Carga de trabalho de enfermagem: análise comparativa de métodos de distribuição diária de pessoal - DIAS, Alana Celeste Campos (2020)
This work aims to analyze the distribution of the nursing workload from the simulation of three methods of daily distribution. It presents three different methods for carrying out the daily staff distribution scale, Method 1, of the equivalent proportion, which is based on the proportional division of beds occupied among technicians or nursing assistants, without considering the degree of dependence of the patient; the method of Menegaz (Method 2) and the method of the Medical Clinic - adapted from the method Menegaz (Method 3), both seek to distribute the workload and not only beds, using a Patient Classification System daily. This is a Simulation Study in four phases: Planning; Modeling; Experimentation; Decision and Conclusion. The data collection for simulation was performed in the medical clinic of a university hospital in the North region of Brazil with the collaboration of 10 nursing technicians, 6 of the morning shift and 4 of the afternoon shift. From the activities described in the Nursing Handbook as the assignment of the mid-level personnel, the professionals were observed and the time of execution of the activities were timed in the period of 30 days. With the information collected, a flowchart representative of the work process was constructed in a shift and inserted in the Software Arena, student version. Three stochastic simulations were carried out, based on the three daily scales from the 1st, 2nd and 3rd daily distribution method, respectively, where the patient distributions among the technicians in the software were included to obtain the workload based on data collected in the collection. As a result, the three methods were compared, supporting the hypothesis that the methods that take into account the degree of dependence of the patients distribute a more egalitarian form to the workload among the nursing team. In the course of this study, limitations related to data collection and appearance of other variables that influenced the object of study appeared, and new hypotheses appeared. Despite this, it was possible to obtain the result that answered the hypothesis suggested in this research. Considering these data and the hypotheses that emerged during the research, other investigations are necessary to deepen the correlation between the degree of dependence of the patient and the workload.